Effects of paricalcitol on calcium and phosphate metabolism and markers of bone health in patients with diabetic nephropathy: results of the VITAL study - Coyne, Daniel W.; Andress, Dennis L.; Amdahl, Michael J.; Ritz, Eberhard; de Zeeuw, Dick (Nephrology, dialysis, transplantation, 2013)
Background - Chronic kidney disease (CKD) is associated with elevations in serum phosphate, calcium-phosphorus product and bone-specific alkaline phosphatase (BAP), with attendant risks of cardiovascular and bone disorders. Active vitamin D can suppress parathyroid hormone (PTH), but may raise serum calcium and phosphate concentrations. Paricalcitol, a selective vitamin D activator, suppressed PTH in CKD patients (stages 3 and 4) with secondary hyperparathyroidism (SHPT) with minimal changes in calcium and phosphate metabolism. - - Methods - The VITAL study enrolled patients with CKD stages 2-4. We examined the effect and relationship of paricalcitol to calcium and phosphate metabolism and bone markers in a post hoc analysis of VITAL. The study comprised patients with diabetic nephropathy enrolled in a double-blind, placebo-controlled, randomized trial of paricalcitol (1 or 2 μg/day). Urinary and serum calcium and phosphate, serum BAP, and intact PTH (iPTH) concentrations were measured throughout the study. - - Results - Baseline demographics and calcium, phosphate, PTH (49% with iPTH <70 pg/mL), and BAP concentrations were similar between groups. A transient, modest yet significant increase in phosphate was observed for paricalcitol 2 μg/day (+0.29 mg/dL; P < 0.001). Dose-dependent increases in serum and urinary calcium were observed; however, there were few cases of hypercalcemia: one in the 1-μg/day group (1.1%) and three in the 2-μg/day group (3.2%). Significant reductions in BAP were observed that persisted for 60 days after paricalcitol discontinuation (P < 0.001 for combined paricalcitol groups versus placebo). Paricalcitol dose-dependent reductions in iPTH were observed. Paricalcitol in CKD patients (±SHPT) was associated with modest increases in calcium and phosphate. - - Conclusion - Paricalcitol reduces BAP levels, which may be beneficial for reducing vascular calcification. - - Trial registration - Trial is registered with ClinicalTrials.gov, number NCT00421733.